Industrial reconversion in productive clusters. Design and active preservation of local know-how - Beatrice Lerma; Eva Vanessa Bruno (Agathón)
The discipline of Design is called upon to contribute to the preservation and transmission of the productive culture of agglomeration economies, such as industrial Districts, clusters and networks, a culture threatened by the tendency to move the supply-chain out of the territory, with a consequent loss of local identity and know-how. The territory, considered as the ‘design-object’ of the study, is analysed through a holistic and exploratory view, which highlights socio-cultural aspects and relations between stakeholders through gigamaps. The economic complexity of the territorial productive capital is systematised with diagrams showing the connections between products according to the productive capacities of companies. Industrial reconversion is the strategy identified to explore and manage emerging technological paradigms, capable of creating new products that convey the local production culture.